PELATIHAN MEDIA CANVA DALAM MENINGKATKAN LITERASI DIGITAL DAN KREATIVITAS ANAK DI DESA SUMBERJAYA - Bena Abimanik; Yoga Candra Maulana; Amin Amin (An-Nizam, 2022)
Education today must improve the quality of learning that is more innovative and creative. Learning media is one of the supporting components in learning, during this pandemic many schools are doing the learning process online because of social distancing restrictions that make the capacity of this school limited. The presentation of interesting, creative, and informative information or news is one of the capital to create information that is easily accepted by readers, in addition, learning media also affects students' learning interests, one example of learning media is by using infographics presented in a visual format. Therefore, the author held a Real Work Lecture Program containing Canva Media Training activities to improve digital literacy and creativity for children which will be held at Griya Pratama Bekasi RT / RW 001/034 Housing, Sumberjaya Village. This activity is carried out for 3 weeks. The goal is that with this training activity, the author wants to teach children who are in Griya Pratama Bekasi RT / RW 001 / 034 Housing, Sumberjaya Village has experience in designing. This activity has provided knowledge to the public/participants about the canva application which can be a reference for making infographic/poster designs, videos, logos, and even learning media as well. In addition, this training also improves the ability of participants in terms of innovative and creative skills.